Surgical Management of Cholelithiasis, A Literature Review - Mishra, Santosh; Dwivedi, Prashant (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Cholelithiasis, commonly called gallstone disease, represents a widespread medical condition characterized by various clinical manifestations, including biliary colic, cholecystitis, and other complications. The article integrates ﬁndings from pivotal studies to thoroughly comprehend the prevailing surgical strategies, outcomes, and prospective advancements in the management of cholelithiasis. MATERIAL AND METHODS Literature search was done from Google Scholar, Pubmed, Medscape and a narrative analysis was performed using keywords cholelithiasis, surgical management. RESULTS Surgical practices for managing cholelithiasis have evolved signiﬁcantly, placing a strong priority on less invasive techniques i.e. Laparoscopic cholecystectomy. Open cholecystectomy is still a crucial surgical option for patients with complicated illnesses such severe inﬂammation, cancer, or anatomical difﬁculties that make laparoscopic procedures impractical. Lithotripsy and dissolution therapy are valuable options for CBDS management, especially for patients unﬁt for surgery. CONCLUSION Surgical management especially laparoscopic cholecystectomy is gold standard for cholelithiasis in terms of hospital stay, surgery time, aesthetics, pain management and postoperative complications.